X-linked West Syndrome and mental retardation - Cersósimo, Ricardo Oscar; Caraballo, Roberto Horacio; Buompadre, María Celeste; Fejerman, Natalio (Journal of Pediatric Neurology, 2005)
X-linked infantile spasms associated with mental retardation have been recognized as a syndrome with an identified gene: ARX. We report a family with eight affected males. Mental retardation was present in all, seven also had epilepsy. In the index case, onset took place in the form of West syndrome. The index case was a boy now six years of age, born from healthy non-consanguineous parents who started at age one month with focal seizures associated with fever. His younger brother had a similar onset. We were not able to examine the other affected males of the family and diagnosis of their type of epilepsy could not be defined. In the first case, the electroencephalogram (EEG) at one month showed slow waves in fronto-temporal regions. Laboratory and imaging studies were normal. Clusters of epileptic spasms with hypsarrhythmia in the EEG appeared at six months of age. The spasms were refractory to treatment. Psychomotor development was severely delayed thereafter. His younger brother also started with focal seizures at one month of age, but a few months later he presented frequent myoclonic seizures associated with generalized spike and spike-wave paroxysms on the EEG. His laboratory work-up and brain imaging were also normal and his seizures have remained refractory to antiepileptic drugs. This child was also mentally retarded. Apparently, there are various phenotypes of epilepsy associated with mental retardation in males in this family. However, our index case seems to have a disease compatible with the diagnosis of X-linked West syndrome.
Keywords: West syndrome; X-linked; epileptic spasms; hypsarrhythmia; mental retardation